Metal Fluoride–Lithium Batteries: 3D Honeycomb Architecture Enables a High‐Rate and Long‐Life Iron (III) Fluoride–Lithium Battery (Adv. Mater. 43/2019). Issue 43 (22nd October 2019) - Wu, Feixiang; Srot, Vesna; Chen, Shuangqiang; Lorger, Simon; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : Metal fluoride–lithium batteries are promising for the fabrication of lighter, thinner, and cheaper next‐generation rechargeable batteries. In article number1905146, Feixiang Wu, Yan Yu, and co‐workers develop a 3D honeycomb architecture to synchronously achieve fast electron and Li + transport in an FeF3 @C cathode. The produced FeF3 @C composite cathodes offer unprecedented rate capability up to 100C and remarkable cycle stability within 1000 cycles.